PENGARUH PRAKTIK KERJA INDUSTRI DAN PERAN BURSA KERJA KHUSUS TERHADAP KESIAPAN KERJA SISWA KELAS XII DPIB SMKN 2 SURABAYA - Catur Ayu Almaidia; Nur Andajani (Jurnal Kajian Pendidikan Teknik Bangunan, 2023)
Vocational high schools is the largest contributor to unemployment in Indonesia based on the level of unemployment by education level. An influencing factor is the job readiness of its graduates. At SMKN 2 Surabaya, there is a practical internship program and a BKK school institution that serves as a service and information channel related to the world of work with students. This study aims to (1) determine the effect of the internship on the job readiness of students in class XII DPIB SMKN 2 Surabaya, (2) determine the effect of the BKK role on the job readiness of students in class XII DPIB SMKN 2 Surabaya, (3) determine the effect of the internship and the BKK role on the job readiness of students in class XII DPIB SMKN 2 Surabaya. This research is an ex post facto research. This research was conducted at SMK Negeri 2 Surabaya with a sample of 101 students in class XII DPIB in the 2023/2024 school year who had carried out practical internships, with the sampling technique using purposive sampling. Data collection using a questionnaire. The classic assumption test uses normality test, linearity test, and multicollinearity test. While hypothesis testing using simple regression test, multiple regression test, T test and F test assisted by SPSS 24.0 for windows. The results of this study are: 1) Prakerin has an influence on the work readiness of XII DPIB class students of SMKN 2 Surabaya by 49.4%. 2) The role of BKK has an influence on the job readiness of XII DPIB students of SMKN 2 Surabaya by 35.4%. 3) Internship and the role of BKK have an influence on the job readiness of XII DPIB students of SMKN 2 Surabaya by 53%.